TaTCP-1, a Novel Regeneration-Related Gene Involved in the Molecular Regulation of Somatic Embryogenesis in Wheat (Triticum aestivum L.) - Li, Feifei; Li, Xiaoyan; Qiao, Meng; Li, Bo; Guo, Dongwei; Zhang, Xiaohong; Min, Donghong (Frontiers in Plant Science, 2020)
The lower regeneration rate of wheat calli is the main factor restricting the development of transgenic wheat plants. Therefore, improving the regeneration rate of wheat callus is a precondition for developing genetic engineering-based wheat breeding approaches. In the present study, we explored the molecular mechanism of wheat regeneration and aimed to establish an efficient system for transgenic wheat. We isolated and identified a regeneration-related gene, TaTCP-1 (KC808517), from wheat cultivar Lunxuan 987. Sequence analysis revealed that the ORF of TaTCP-1 was 1623bp long encoding 540 amino acids. The TaTCP-1 gene was expressed in various wheat tissues. Further, the level of TaTCP-1 expression was higher in calli and increased gradually with increasing callus induction time, reaching a peak on the 11th day after induction. Moreover, the expression level of TaTCP-1 was higher in embryogenic calli than in non-embryonic calli. The TaTCP-1 protein was localized to the nucleus, cytoplasm, and cell membrane. The callus regeneration rate of wheat plants transformed with TaTCP-1-RNAi reduced by 85.09%. In contrast, it increased by 14.43% in plants overexpressing TaTCP-1. In conclusion, our results showed that TaTCP-1 played a vital role in promoting wheat regeneration, and regulated the somatic embryogenesis of wheat. These results may have implications in the genetic engineering of wheat for improved wheat production.